The role of calcium in the action and release of vasopressin and oxytocin from CNS neurones/terminals to the heart - Dayanithi, G; Viero, C; Shibuya, I (Journal of physiology and pharmacology, 2008)
The main long-range goal of this study is to analyse how electrical activity generated at somata is transformed into chemical signals at nerve terminals. We try to achieve this goal by examining, at the level of membrane and molecular mechanisms, the steps considered to be involved in stimulus-secretion coupling: how neurotransmitters are released in response to depolarisation of the nerve terminal membrane. We have demonstrated over several years the release of the neuroactive peptides, vasopressin and oxytocin and the role for Ca(2+), in the hypothalamic-neurohypophysial system (HNS) of the rat and also in cardiac tissues (from the brain to the heart). This study was performed using both a well-characterized preparation of pure, isolated neurohypophysial nerve terminals, a preparation of isolated hypothalamic magnocellular neurones and isolated cardiac myocytes. Furthermore, the intact HNS would affords the unique opportunity of comparing the somata and terminals of the same CNS neurones. This article plans to build on the this wealth of information already gathered on isolated, individual terminals/somata in order to analysis of the physiology of the whole, intact system in situ. We show some of the well established data to explain: i) why are different patterns of electrical activity (i.e. bursts) best for AVP vs. OT release in the intact HNS, ii) are there any other parameters, transmitters, messengers, hormones and drugs that could play an important role, iii) is Ca(2+) important to understand this physiology, and finally iv) what do we learn from the comparison to the cardiac system?
Keywords: vápníková signalizace; Animals; Heart; Arginine Vasopressin; Hypothalamo-Hypophyseal System; srdce; lidé; neurony; arginin vasopresin; vápník; oxytocin; systém hypotalamus-hypofýza; Central Nervous System; Neurons; Oxytocin; Calcium; Calcium Signaling; zvířata; centrální nervový systém; Humans